2020
DOI: 10.1176/appi.ps.201900283
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peer-Supported Computer-Based CBT for Depression Among Veterans in Primary Care

Abstract: This study tested whether computerized cognitivebehavioral therapy for depression supported by a peer specialist with lived experience of depression (PS-cCBT) improves mental health-related outcomes for primary care patients.Methods: In the U.S. Department of Veterans Affairs, primary care patients with a new diagnosis of depression (N=330) were randomly assigned to 3 months of PS-cCBT or a usualcare control condition. Linear mixed-effects models were used to assess differences in depression symptoms, general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…There were 12 RCTs testing TBIs against TAU [ 34 , 35 , 39 - 41 , 51 , 57 , 63 , 64 , 72 , 74 , 92 ], 8 of which explicitly stated that TAU was also administered in the TBI condition [ 34 , 35 , 39 - 41 , 57 , 74 , 92 ]. TBIs were delivered either with [ 39 - 41 , 51 , 63 , 72 , 74 , 92 ] or without [ 34 , 57 ] guidance or they were therapist-administered [ 35 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 12 RCTs testing TBIs against TAU [ 34 , 35 , 39 - 41 , 51 , 57 , 63 , 64 , 72 , 74 , 92 ], 8 of which explicitly stated that TAU was also administered in the TBI condition [ 34 , 35 , 39 - 41 , 57 , 74 , 92 ]. TBIs were delivered either with [ 39 - 41 , 51 , 63 , 72 , 74 , 92 ] or without [ 34 , 57 ] guidance or they were therapist-administered [ 35 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 12 RCTs testing TBIs against TAU [ 34 , 35 , 39 - 41 , 51 , 57 , 63 , 64 , 72 , 74 , 92 ], 8 of which explicitly stated that TAU was also administered in the TBI condition [ 34 , 35 , 39 - 41 , 57 , 74 , 92 ]. TBIs were delivered either with [ 39 - 41 , 51 , 63 , 72 , 74 , 92 ] or without [ 34 , 57 ] guidance or they were therapist-administered [ 35 , 64 ]. TAU consisted of care by a general practitioner [ 34 , 40 , 41 , 57 , 92 ], a heterogeneous mix of treatment options depending on resources and routines [ 51 , 63 , 72 , 74 ], care by community-based outpatient clinics and any non-Veterans Affairs facilities [ 64 ], and antenatal [ 39 ] or postpartum care [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17−30 Study participants comprised a majority sample of White (15 studies) 18,22,24−36 male individuals (15 studies), 19,22,23,25 −30,33−35,37−39 with a mean age of 45 years (age range = 30.6−55.3 years) who were single, divorced, or never married (6 studies). 19,23,28,31,37,38 Nonspecified serious mental illness (12 studies), [17][18][19][20][21]23,27,28,31,32,35,36 depression (11 studies), 17,[20][21][22]24,[31][32][33]35,37,39 schizophrenia/ schizoaffective disorder (11 studies), 17,20,21,23,27, 31,32,35 −37,39 and SUD (11 studies) 18,19,23,[25][26][27][29][30][31]34,38 were the most prevalent behavioral health conditions experienced by the study participants. Other frequently observed behavioral health conditions were bipolar disorder (8 studies) 17,20,…”
Section: (Available Online)mentioning
confidence: 99%
“…In ex-service personnel, previous research has demonstrated peer-to-peer interventions or peer-support programs may help to support reintegration to civilian life (Drebing et al, 2018;Westwood et al, 2010), reduce stigma (Kivari et al, 2018), enhance treatment adherence or engagement (Goetter et al, 2018;Ray et al, 2017), and improve treatment outcomes (Jain et al, 2016;Travis et al, 2010). Specifically, peer-support may help to improve engagement and outcomes related to CBT (Nelson et al, 2014;Pfeiffer et al, 2020;Westwood et al, 2010). In a recent study by Pfeiffer and colleagues (2020), peer encounters in association with an online peer-support CBT program for veterans was positively associated with the number of CBT modules completed.…”
Section: Peer-to-peer Interventionsmentioning
confidence: 99%